Tracing the Adoption and Effects of Open Science in Communication Research*. (19th August 2021) - Markowitz, David M; Song, Hyunjin; Taylor, Samuel Hardman
Abstract: A significant paradigm shift is underway in communication research as open science practices (e.g., preregistration, open materials) are becoming more prevalent. The current work identified how much the field has embraced such practices and evaluated their impact on authors (e.g., citation rates). We collected 10, 517 papers across 26 journals from 2010 to 2020, observing that 5.1% of papers used or mentioned open science practices. Communication research has seen the rate of nonsignificant p-values (p > .055) increasing with the adoption of open science over time, but p-values just below p < .05 have not reduced with open science adoption. Open science adoption was unrelated to citation rate at the article level; however, it was inversely related to the journals' h-index. Our results suggest communication organizations and scholars have important work ahead to make open science more mainstream. We close with suggestions to increase open science adoption for the field at large.